Benchmarking process of the knowledge economy pillars for sustainable development in Saudi Arabia - Alajmi, Reema Ghazi (Journal of Economic, Administrative and Legal Sciences, 2019)
The fluctuations in oil price limit the ability to maintain growth in the long-run for oil-producing countries with heavy economic dependence on oil revenues. The Saudi government has initiated economic strategies with the aim of diversifying the economic base. Thus, the knowledge economy is important for Saudi Arabia in terms of offering other economic drivers to achieve sustainable economic development. So, the aim of this study is to assess Saudi’s readiness for the knowledge economy through presenting the current situation of knowledge economy pillars in the country and then offer recommendations that could lead the Saudi Arabia to sustainable development. The analytical framework in this study is a comparative and benchmarking approach using AKI 2016, along with other indicators to assess Saudi readiness in respect of the key knowledge economy pillars. The study findings show that Saudi Arabia has achieved positive progress in knowledge economy pillars but the overall performance in knowledge drivers is not as competitive compared with the other members of the benchmarking group. A knowledge economy strategy that is comprehensive and integrated is required, in which all knowledge economy indicators are equally supported; setting specific time targets to implement the national strategy for the transition towards the knowledge economy will also be beneficial.